Post-Lie Algebra Structures on the Lie Algebra gl(2,C) - Yuqiu Sheng; Xiaomin Tang (Abstract and Applied Analysis)
The post-Lie algebra is an enriched structure of the Lie algebra. We give a complete classification of post-Lie algebra structures on the Lie algebra gl(2,C) up to isomorphism.